O socjotechnicznych, a także prakseologicznych korzeniach doradztwa politycznego - Scheffs, Łukasz (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2016)
Artykuł traktuje przede wszystkim o doradztwie (konsultingu) politycznym i znaczeniu konsultantów politycznych w organizacji politycznej. Z oczywistych względów dotyka też zagadnień związanych z praktycznym zastosowaniem wiedzy naukowej. Autor dokonuje w nim próby analizy rozumienia pojęcia doradztwa politycznego poprzez wskazanie jego zależności z takimi terminami jak socjotechnika, doradztwo komunikacyjne, doradztwo osobiste, doradztwo merytoryczne i kampania wyborcza.

The main topic of the paper is political consulting and the significance of political consultants in political organizations. For obvious reasons the paper also addresses the issues of academic knowledge being implemented in practice. The author undertakes to analyze how the notion of political consulting is understood by indicating its relation to such notions as social engineering, communication consulting, personal consulting, thematic consulting and election campaigns.
About social engineering and praxeological roots of political consulting
Keywords: doradztwo polityczne; konsulting polityczny; socjotechnika; political consulting; social engineering